Identification of resources and training needs for the implementation of the bilingual policy in the three districts of Cagayan - Manalo, Elizabeth Taruc 1943- (1976)
The aim of this study was to identify the resources and training needs for the implementation of the bilingual policy in the three districts of Cagayan, namely Pamplona, Sanchez Mira and Claveria.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Education, Bilingual -- Cagayan; Elementary school teachers -- Cagayan